Management of choroidal/ciliary body metastasis in the era of targeted cancer therapy - Evbuomwan, Moses O.; Bhuyan, Rupak; Uzomah, Uwajachukwumma A.; Jamshidi, Farzad; Anderson, Carryn; Boldt, H. Culver; Binkley, Elaine (Frontiers in Oncology, 2024)
IntroductionChoroidal metastases from systemic malignancies are the most common intraocular malignancies in adults. External beam radiation (EBR) has historically been first-line therapy for metastatic tumors to the choroid. However, good responses have been described with newer targeted biologics. The optimal management strategy for patients with choroidal metastatic tumors in the era of targeted cancer therapy is not known. We aim to describe management of these tumors in a “real-world” setting using both radiation and systemic therapy.MethodsWe conducted a retrospective review of patients with choroidal/ciliary body metastases managed by the ocular oncology service at our institution over a five-year period. Demographic data, tumor type, treatment, visual outcomes, and mortality data were recorded.Results26 patients (33 eyes) with choroidal/ciliary body metastasis were identified. Primary malignancies included lung (8) breast (8), renal (3), esophageal (3), carcinoid (2), squamous cell carcinoma of the tonsil (1), and testicular cancer (1). Average time from diagnosis of ocular metastasis to death was 8 months (1-34). 20 eyes were treated with EBR and 13 eyes were treated with other modalities. Final logMAR visual acuity for eyes treated with radiation was 0.11 (0-3). Final visual acuity for eyes treated with other modalities was 0.18 (0-.70), with local tumor control in 20/23 eyes that had follow up after treatment. The difference between final visual acuity in these groups was not visually significant p=0.48.ConclusionPatients with choroidal/ciliary body metastasis treated with either EBR or systemic therapy can have good visual outcomes. More work needs to be conducted to determine the optimal first-line treatment of ocular metastasis for specific tumor subtypes.